Impulsive noise mitigation based on iteration adaptive approach in underwater acoustic communication - Guili ZHOU; Youming LI; Mingchen YU; Xiaoli WANG (Dianxin kexue)
Focusing on the impulsive noise mitigation in underwater acoustic communication,an impulsive noise mitigation method based on iteration adaptive approach was proposed.Firstly,by utilizing the orthogonality of the subcarriers in OFDM system,both the impulsive noise and background noise were separated from the signals.Then null tones matrix was used to construct a steering matrix and get the impulsive noise interference covariance matrix.Furthermore,a cost function based on weighted least squares approach was proposed and a close form expression for the impulsive noise was derived.Finally,the impulsive noise was mitigated by substracting the estimation of the impulse noise in the received signal.Simulation results show that the proposed algorithm can reduce the bit error rate (BER) efficiently and provide better performance,especially in high signal to impulsive noise ratio (SINR) case.